2011
DOI: 10.1002/ca.21254
|View full text |Cite
|
Sign up to set email alerts
|

Branching pattern of the external branch of the superior laryngeal nerve and its clinical importance

Abstract: The external branch of the superior laryngeal nerve gives off many branches above the upper pole of the thyroid gland. Differentiating the branch innervating the cricothyroid muscle from the others may be important during surgery. Therefore, we aimed to demonstrate the branching pattern of this nerve in detail. In 34 human cadavers (59 sides), branches of the nerve were exposed and measurements related to them and neighboring structures were made. A cricothyroidal branch was present on all sides. This branch p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In cadaveric studies it has been shown that the EBSLN gives off many branches above the upper pole of the thyroid gland. The clinically important cricothyroidal branch has been found to be thicker and it pierces the IC muscle about 3.9–17.6 mm above, 3.1–9.9 mm below, or at the level of the upper border of thyroid gland [9]. One or two thyroidal and pharyngeal branches arise from the EBSLN which may be mistaken as cricothyroidal branch; however, these are very thin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cadaveric studies it has been shown that the EBSLN gives off many branches above the upper pole of the thyroid gland. The clinically important cricothyroidal branch has been found to be thicker and it pierces the IC muscle about 3.9–17.6 mm above, 3.1–9.9 mm below, or at the level of the upper border of thyroid gland [9]. One or two thyroidal and pharyngeal branches arise from the EBSLN which may be mistaken as cricothyroidal branch; however, these are very thin.…”
Section: Discussionmentioning
confidence: 99%
“…One or two thyroidal and pharyngeal branches arise from the EBSLN which may be mistaken as cricothyroidal branch; however, these are very thin. Hence, during the routine thyroidectomy the thicker cricothyroidal branch has to be safeguarded [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Another hypothesis may be an insufficient blood support from the branches of STA to the nerve, especially the posterior and the anterior glandular branches, due to a devascularization during STA ligation. 14 The different relationships of the EBSLN with the other anatomical structures led to many classifications with the aim of detecting the nerve. The Cernea classification, which analyzes the relationship between the nerve and the STA, remains the simplest.…”
Section: Discussionmentioning
confidence: 99%
“…1 Anatomical relationship between RLN and ITA is very important in order to preserve the RLN. 2,3 Mostly the morbidity is due to technical failure(inadequate anatomical knowledge ,lack of surgical skill & experience, distorted anatomy as in cancer & large multinodular goiter) to identify the vital structures and the variations in the surgical anatomy. Several studies have been published revealing the anatomy of the RLN in thyroid surgery.…”
Section: Introductionmentioning
confidence: 99%